1994
DOI: 10.1117/12.185903
|View full text |Cite
|
Sign up to set email alerts
|

<title>Design of psychovisual quantizers for a visual subband image coding</title>

Abstract: In order to specify the optimal psychovisual quantizer associated to a given visual subband decomposition scheme [1], a new methodology has been developped. Psychovisual experiments based on the visibility of the quantization noise, have been conducted. The complex signals used, have been caracterised by the local bandlimited contrast. The main finding of this study is that the quantizers are, in the chosen space contrast ,of a linear type. The quantization intervals contrast, obtained with a given observer, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Eight bits are assigned and used for linear quantization of each descriptor value. The linear quantization used in the paper is written as (11) where D quant is a quantized descriptor value, D nonquant is the value of the feature, and max β and min β are the maximum and minimum values of features in the database. Note that q_level is set to 255.…”
Section: Quantization Of Texture Descriptormentioning
confidence: 99%
See 1 more Smart Citation
“…Eight bits are assigned and used for linear quantization of each descriptor value. The linear quantization used in the paper is written as (11) where D quant is a quantized descriptor value, D nonquant is the value of the feature, and max β and min β are the maximum and minimum values of features in the database. Note that q_level is set to 255.…”
Section: Quantization Of Texture Descriptormentioning
confidence: 99%
“…It provided higher retrieval accuracy for the testing data sets. Therefore, the homogeneous texture descriptor described in this paper was selected as the normative MPEG-7 homogeneous texture descriptor in the Visual part of the MPEG-7 final committee draft [11]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…In previous study [8], psychophysical experiments have been performed to evaluate quantization impairment perception (at normalized viewing distance of 4H) upon natural pictures. In the local band limited contrast space it was shown that contrast must always be uniformly quantized in order to achieve a just noticeable quantization noise (the quantization step Aj being dependent of the visual subband considered).…”
Section: Y)mentioning
confidence: 99%
“…It is more convenient here to study the visibility produced by quantization of the content of a particularly subband rather than the visibility of any increments or any white gaussian noises. Previously, we have shown 5 that perception of quantization noise on L ij at location (m,n) is directly dependent on the ratio between L ij and the average luminance at this location. This latter is computed from the subbands having a lower radial frequency.…”
Section: Quantizationmentioning
confidence: 99%
“…Here we are concerned with Krauskopf's directions A, Cr1, Cr2. For each components, it can be identified both analysis and quantization stages like we have done in previous works 4,5 . Unfortunately, perceptual components are not independent and some interactions subsist between luminance and chrominance.…”
Section: Introductionmentioning
confidence: 99%